Revitalizing Badoncek and Jimpitan: Culture-Based Approaches to Waqf Fundraising in Indonesia - Haris, Gusnam; Wira, Ahmad; Syukria, Alfi; Augusna, Wahyuni Lely; Ismail, Shafinar; Afrida, Yenti (Mazahib, 2025)
Culture-based waqf fundraising is a strategic approach that utilizes a community’s cultural, religious, and social values to support waqf institutions. In Indonesia, local traditions such as Badoncek and Jimpitan reflect communal solidarity and can serve as effective mechanisms for waqf fundraising. This study highlights the importance of integrating local cultural practices to enhance the effectiveness, sustainability, and socio-economic impact of waqf in contemporary society. Using a qualitative, thematic analysis, the research draws on interviews with government officials, waqf practitioners, and academics to examine the opportunities and risks of culture-based waqf fundraising. The findings reveal that Badoncek and Jimpitan’s practices present significant opportunities and challenges when applied to waqf fundraising. They enable rapid fund collection, strengthen social cohesion, and maintain community engagement due to their deep-rooted cultural values and ongoing preservation. However, potential risks include limited scalability, a lack of standardized management, and dependency on local participation. Incorporating cultural elements into waqf fundraising can enhance trust, credibility, and long-term community commitment by respecting local traditions and values. They also raise public awareness about the importance and social impact of waqf. Therefore, integrating local culture, such as Badoncek and Jimpitan, into waqf fundraising strategies can strengthen community-based economic empowerment and sustain waqf institutions.